(untitled) (Studia Prawnicze / The Legal Studies, 1995)
Konieczne jest znowelizowanie art. 58 § 1 k.r.o. przez dodanie zdania głoszącego, że "bezpośrednia piecza nad rodzeństwem powinna być w miarę możności powierzona jednemu z rodziców". Można tę poprawkę do k.r.o. sformułować także inaczej, a mianowicie: "bezpośrednia piecza nad rodzeństwem powinna być powierzona jednemu z rodziców, chyba że szczególne względy przemawiają za innym rozstrzygnięciem". Wypadałoby zmienić art. 106 k.r.o. dodając do niego drugie zdanie o następującej treści: "Powinien mieć zwłaszcza na uwadze, aby bezpośrednia piecza nad rodzeństwem została powierzona jednemu z rodziców, jeżeli szczególne względy nie przemawiają za innym rozstrzygnięciem." Przy okazji zmiany przepisu art. 106 k.r.o. należałoby usunąć z niego słowa "w razie zmiany okoliczności", gdyż pozostaje to w sprzeczności z podstawową przesłanką w nim zawartą, tj. uwzględniania dobra dziecka. Nie można przecież oddalić wniosku tylko dlatego, że okoliczności nie zmieniły się od czasu wydania wyroku rozwodowego, nie badając, czy podważane rozstrzygnięcie o władzy rodzicielskiej zawarte w wyroku rozwodowym jest sprzeczne z dobrem dziecka. De lege lata proponuje się: • upowszechnienie wykładni art. 58, 114 § 2 i 151 k.r.o., przyjmując, że wyrażona w art. 114 § 2 i 151 k.r.o. intencja ustawodawcy dotycząca rodzeństwa obejmuje również art. 58 § 1 k.r.o. i powinna być uwzględniana przy jego stosowaniu oraz przy stosowaniu art. 577 k.p.c., który dopuszcza możliwość zmiany przez sąd opiekuńczy swego postanowienia, nawet jeśli jest ono prawomocne, kiedy wymaga tego dobro dziecka; • ustanowienie w ramach wykładni pojęcia "dobro dziecka" reguły interpretacyjnej stanowiącej, że rozdzielenie rodzeństwa jest sprzeczne z dobrem dziecka generalnie, chyba że szczególne względy przemawiają za takim rozstrzygnięciem; dotyczyłoby to nie tylko instytucji rozwodu i w związku z nim sposobu sprawowania władzy rodzicielskiej nad dziećmi przez rozwodzących się rodziców, ale również przysposobienia oraz opieki, co do której nie ma wątpliwości ze względu na omówiony wyżej art. 151 k.r.o. It is necessary to amend Article 58(1) of the Family and Guardianship Code by adding a sentence stating that “direct custody of siblings should, as far as possible, be entrusted to one of the parents”. This amendment to the Family and Guardianship Code could also be worded differently, namely: “direct custody of siblings should be entrusted to one of the parents, unless special considerations favour a different outcome”. It would be advisable to amend Article 106 of the Family and Guardianship Code by adding a second sentence to read as follows: “It should have particular regard to ensuring that direct custody of siblings is entrusted to one of the parents if special considerations do not support a different outcome”. When amending the provision of Article 106 of the Family and Guardianship Code, the words “in case of a change of circumstances” should be removed from it, as this contradicts the basic premise contained therein, i.e. to take into account the welfare of the child. After all, it is not possible to dismiss a motion simply because the circumstances have not changed since the divorce judgement, without examining whether the challenged parental authority determination in the divorce judgement is contrary to the child’s best interests. De lege lata is proposed: • to generalise the interpretation of Articles 58, 114 § 2 and 151 of the Family and Guardianship Code, assuming that the intention of the legislator regarding siblings expressed in Articles 114 § 2 and 151 of the Family and Guardianship Code also extends to Article 58 § 1 of the Family and Guardianship Code and should be taken into account in its application and in the application of Article 577 of the Family and Guardianship Code, which allows the guardianship court to amend its order, even if it is final, when the best interests of the child require it; • to establish, as part of the interpretation of the concept of “the best interest of the child”, an interpretative rule to the effect that the separation of siblings is contrary to the best interest of the child in general, unless there are specific grounds for doing so; this would apply not only to the institution of divorce and, therefore, to the exercise of parental authority over the children by the divorcing parents, but also to adoption and guardianship, about which there is no doubt on account of Article 151 of the Family and Guardianship Code, discussed above.